Analisis Pengaruh Nilai Perusahaan, Penghindaran Pajak, dan Profitabilitas Terhadap Peluang Investasi - Astriani, Elsa Yolanda; Ramadhan, Yanuar (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to determine the effect of Firm Value, Tax Avoidance, and Profitability on Investment Opportunities. This study uses quantitative research. This study uses agency theory. This study uses Trading companies in the Retailing, Food and Staples Retailing subsector listed on the Indonesia Stock Exchange for the 2020-2023 period as research samples. Through a purposive sampling method, 11 companies were selected over the four-year study period, resulting in a total of 44 sample data. Data analysis uses multiple linear regression methods with Microsoft Excel and SPSS as supporting software for data analysis. The data used are secondary data derived from the company's annual report accessed through http://www.idx.co.id/ and the company's website. The results of this study indicate that Firm Value, Tax Avoidance, and Profitability have a positive and significant effect on Investment Opportunities. This indicates that good market perception and investor confidence are key factors in facilitating funding and realizing investment opportunities. Tax avoidance confirms that this practice triggers agency conflicts and creates risks that hinder company growth. High profits also influence investors' investment decisions. Therefore, these findings emphasize the importance of creating transparent long-term value and avoiding risky actions to maximize a company's investment opportunities.